Families in an Era of Increasing Inequality : Diverging Destinies - Amato, Paul R.; Booth, Alan; McHale, Susan M.; Van Hook, Jennifer (National Symposium on Family Issues,, 2015)
The widening gap between the rich and the poor is turning the American dream into an impossibility for many, particularly children and families. And as the children of low-income families grow to adulthood, they have less access to opportunities and resources than their higher-income peers--and increasing odds of repeating the experiences of their parents. Families in an Era of Increasing Inequality probes the complex relations between social inequality and child development and examines possibilities for disrupting these ongoing patterns. Experts across the social sciences track trends in marriage, divorce, employment, and family structure across socioeconomic strata in the U.S. and other developed countries. These family data give readers a deeper understanding of how social class shapes children's paths to adulthood and how those paths continue to diverge over time and into future generations. In addition, contributors critique current policies and programs that have been created to reduce disparities and offer suggestions for more effective alternatives. Among the topics covered: Inequality begins at home: the role of parenting in the diverging destinies of rich and poor children. Inequality begins outside the home: putting parental educational investments into context. How class and family structure impact the transition to adulthood. Dealing with the consequences of changes in family composition. Dynamic models of poverty-related adversity and child outcomes. The diverging destinies of children and what it means for children's lives. As new initiatives are sought to improve the lives of families and children in the short and long term, Families in an Era of Increasing Inequality is a key resource for researchers and practitioners in family studies, social work, health, education, sociology, demography, and psychology.